2019
DOI: 10.3389/fphar.2019.01396
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Immunoregulatory Effects of Azelaic Acid Against Acute Myeloid Leukemia via the Activation of Notch Signaling Pathway

Abstract: Acute myeloid leukemia (AML) is a common type of hematological malignancy that can progress rapidly. AML has a poor prognosis and a high incidence of relapse due to therapeutic resistance. Azelaic acid (AZA), a small molecular compound is known to exhibit antitumor effect on various tumor cells. This study aimed to evaluate the antiproliferative and immunoregulatory effects of AZA against AMLviathe activation of the notch signaling pathway. We found that AZA can inhibit the proliferation of AML cells. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…Azelaic acid has antimicrobial and anti-inflammatory properties finding application in the treatment of skin diseases. Furthermore, its activity against several tumor cells has also been documented [41].…”
Section: Discussionmentioning
confidence: 99%
“…Azelaic acid has antimicrobial and anti-inflammatory properties finding application in the treatment of skin diseases. Furthermore, its activity against several tumor cells has also been documented [41].…”
Section: Discussionmentioning
confidence: 99%
“…Its derivatives such as hydroquinone 5-O-cinnamoyl ester and some alkyl and prenylated derivatives have also been reported to have cytotoxic activities against lung cancer [20][21][22], meaning that more optimization of the compound has a potential to develop more drug lead options against cancers. Nonanedioic acid (2) has antitumor properties in humans [23], antineoplastic and antileukemic activities [24], immunoregulatory and antiproliferative activities against cancer cells [25,26], and cytotoxic activities and anti-inflammatory and antioxidant activities [27]. Some of its derivatives have also shown to be active against cancers [26] which give a good promise of its usefulness in drug development against cancers and other diseases.…”
Section: Drug Development Prospects Of the Isolatesmentioning
confidence: 99%
“…In addition, Notch is an important regulator of immune cell development and function [ 58 ]. Our previous study had identified that AZA could activate the Notch signaling pathway and enhance the cytotoxicity of immune effector cells against AML [ 59 ]. However, whether AZA can alleviate immunosuppression in the tumor microenvironment via the regulation of Prdxs and Notch requires further study.…”
Section: Discussionmentioning
confidence: 99%